Safety management of organisations in the context of the ISO 9000 quality management systems - Dąbrowska-Świder, Małgorzata; Piotrowski, Kazimierz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The purpose of this article is to present how modern organisations enhance their safety using quality management systems. The paper evaluates the impact of the ISO 9001:2015 requirements on the level of safety of the organisation. It cites arguments both in favour, as well as against, the implementation of the standards. At the same time, the requirements of the standard, which can serve not only to ensure the safety of the organisation’s operations and management, but also to achieve an appropriate level of development, were also evaluated. The essential elements for ensuring the safety of the organisation are presented in relation to selected aspects of the standard, with a particular emphasis on activities related to the need to analyse risks and opportunities to ensure the success of the organisation.